ChemInform Abstract: Regiospecific Synthesis of N2‐Aryl 1, 2, 3‐Triazoles from 2, 5‐Disubstituted Tetrazoles via Photochemically Generated Nitrile Imine Intermediates. Issue 16 (April 2015) - Stewart, Sam; Harris, Robert; Jamieson, Craig
Abstract The preparation of the substrates by copper‐catalyzed coupling of 5‐aryl‐tetrazoles with aryl boronic acids to the corresponding 2, 5‐diaryltetrazoles is described.